2018
DOI: 10.1159/000489487
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Irritable Bowel Syndrome: The Efficacy of the Low Fodmap Diet for Improving Symptoms in Inflammatory Bowel Diseases and Celiac Disease

Abstract: Background and Aim: To evaluate the usefulness of a low FODMAP (Fermentable Oligosaccharides, Disaccharides, Monosaccharides, and Polyols) diet on patients with irritable bowel syndrome (IBS), non-active inflammatory bowel diseases (IBD), and celiac disease (CD) on a gluten-free diet (GFD). Methods: Dietetic interventional prospective study. IBS, IBD, and CD subjects were evaluated to check if they fulfilled the Rome III criteria. Each subject was educated to follow a low FODMAP diet after being evaluated by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The involuntary, and undiscovered, ingestion of gluten cannot be considered responsible for the appearance of symptoms in CD patients on a GFD. If these symptoms are clinically relevant, it is therefore necessary to look for their cause as they could be caused either by a condition associated with CD, and not yet discovered, or by one of the fearsome complications of CD (26)(27)(28) . We conclude that the involuntary ingestion of minimal quantities of gluten does not have a role in the origin of symptoms in patients with CD on a GFD.…”
Section: Discussionmentioning
confidence: 99%
“…The involuntary, and undiscovered, ingestion of gluten cannot be considered responsible for the appearance of symptoms in CD patients on a GFD. If these symptoms are clinically relevant, it is therefore necessary to look for their cause as they could be caused either by a condition associated with CD, and not yet discovered, or by one of the fearsome complications of CD (26)(27)(28) . We conclude that the involuntary ingestion of minimal quantities of gluten does not have a role in the origin of symptoms in patients with CD on a GFD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional gastrointestinal disorders, such as irritable bowel syndrome (IBS) and gastrointestinal dysmotility, are more prevalent in individuals with CD [23,24] and should not be overlooked as a cause of persisting symptoms in individuals with normal repeat duodenal histology. For these individuals, a low fermentable oligo-, di-, mono-saccharide and polyol (FODMAP) diet may improve symptoms and quality of life [25,26]. In one study, 41 CD patients with IBS who had been on a GFD for at least 1 year demonstrated significant improvement in IBS-symptom severity scores after 3 months on the low FODMAP diet [25].…”
Section: An Associated Conditionmentioning
confidence: 99%
“…For these individuals, a low fermentable oligo-, di-, mono-saccharide and polyol (FODMAP) diet may improve symptoms and quality of life [25,26]. In one study, 41 CD patients with IBS who had been on a GFD for at least 1 year demonstrated significant improvement in IBS-symptom severity scores after 3 months on the low FODMAP diet [25]. The benefits of a low FODMAP diet have also been shown in a recent randomized controlled trial; 50 patients with CD and persisting symptoms were randomized to follow either a regular GFD (R-GFD, n = 25) or a low FODMAP GFD (LF-GFD, n = 25) for 21 days.…”
Section: An Associated Conditionmentioning
confidence: 99%
“…Currently, reduced macronutrient intakes are less common in these patients, whereas deficits in micronutrients, such as iron, copper, selenium, magnesium, zinc, vitamins, and antioxidants (vitamins C, E, beta carotene, glutathione, taurine) can occur frequently [8][9][10][11][12][13][14][15][16], even in apparently well-nourished patients [13]. Some food group restrictions, such as dairy products and/or fruit and vegetables, are pursued by patients to control their symptoms [10,17]. Additionally, appetite sensation could dramatically change, especially with active disease, in which patients experience less hunger and more satiety [18].…”
Section: Introductionmentioning
confidence: 99%